Rai bhoʻ Ne ʼOṅʻ cu choṅʻʺ taṅʻ pra so Phakʻchacʻ toʻ lhanʻ reʺ samuiṅʻʺ vaṅʻ cā tamʻʺ myāʺ - Ne ʼOṅʻ, Rai bhoʻ (Paṅʻʺ ya Cā pe Tuikʻ, 1962)
Collection of documents relating to anti-fascist movement against the Japanese occupation, 1942-1945 in Burma.